Se quiser, é assim : uma análise léxico-gramatical da representação feminina em letras de forró eletrônico - Rodrigues, Cláudia Caminha Lopes (2010)
Being part of the daily life of societies, music entertains, but it also contributes to build personalities and to shape society, as it allows listeners to memorize the content, contributing to the assimilation and consolidation of concepts, ideas and beliefs (FERREIRA, 2005). Forró is a current musical style. One of its types, the electronic forró, emerged in the 1990s. It was inspired by country music and axé music. It uses electronic instruments such as keyboards and synthesizers (SILVA, 2003) and this is the reason why it is named eletronic . Women are present in contemporary electronic forró in the names of bands, in lyrics and as singers or dancers in the bands. Considering that lyrics are expressions of language and, as such, convey meaning, reflect and influence human attitude towards the world (BLOOR, 1995) this study aims to examine the representation of women in some electronic forró lyrics. In order to do so, the data are analysed from the perspective of the Systemic Functional Linguistics, more specifically, from the perspective of the Systems of Mood and Transitivity (HALLIDAY, 1994; MATHIESSEN & HALLIDAY, 2004). The results indicate that five lyrics from a total of six confirm the hypotheses: women are represented either as an object of men s sexual pleasure, or as the object of their love, or even as the cause of their suffering. It is hoped that this study will contribute to a better understanding of female representation(s) in the context of electronic forró, by revealing some of those representations.